Developing an Interactive Book about Healthy Food Education to Students at Al Ikhlas Konggo Kindergarten - Munisa; Virdyra Tasril; Rizky Vita Losi; Desmila Fajaria (ASIAN PUBLISHER, 2024)
Early childhood is an individual with an age range of 0 to 6 years who is in the early developmental stages of childhood which still has a unique character so that it must be able to understand it in detail. Early childhood can be introduced to many things, for example about the importance of healthy food through interesting and interactive storybooks. Nutrition education should start at an early age to build healthy eating patterns or habits. Interactive books can be the right solution because they can attract children's attention to learning and interactive books are considered in accordance with the characteristics of learning in children aged 3-5 years (pre-reading). The type of research used in this study was research and development (R&D). The data analysis approach using descriptive statistics was used to assess the feasibility of interactive learning media for children's health and nutrition education. Based on the data results, the average score was 92.01% in the very decent category. This demonstrated that the students' interactive book was thought to be quite feasible. It was also found that the practicality questionnaire yielded an average score of 95.58%. This demonstrated how useful the students' interactive book was. This interactive book is designed with the aim of being an educational medium for children aged 3-5 years in an effort to introduce healthy food types that can help stimulate motor movements in children.